On the insolubility of one drawing problem - Kirjackis, Jevgenijus; Mazėtis, Edmundas; Melničenko, Grigorijus (Lietuvos matematikos rinkinys, 2015)
It is shown in the article that, in general, it is not possible to draw a triangle using a compass and a straightedge given an angle, and a bisector and a median drawn from the vertex of another angle. It is shown in which particular cases a triangle can be drawn.